Pendekatan Ibadah sebagai Model Supervisi untuk Meningkatkan Kinerja Guru Pendidikan Agama Islam - Herman Herman; Jamaluddin Idris (DAYAH: Journal of Islamic Education, 2020)
The worship approach is one of the supervision models that make worship values a basic principle for PAI supervisors in performing the main tasks and functions (Tupoksi) to supervise the improvement of PAI teacher's performance. The problem that arises is that PAI supervisors are still less able to apply the values of worship when conducting supervisory duties to PAI teachers so that the performance of PAI teachers declines according to stakeholders and community perceptions. This study aims to describe the worship approach as a supervision model in improving the performance of PAI teachers in Nagan Raya Regency Junior High School. This research uses a qualitative descriptive approach and employs three data collection techniques, namely observation, interviews, and documentation studies. While data analysis techniques will be based on the opinion of Miles, and Huberman, including 1) data reduction, 2) display/ presentation of data, and 3) drawing conclusions or data verification. In this research, the validity of the data will be analyzed by using four criteria, namely the degree of trust (credibility), transferability, dependability, and confirmability. The results showed that the PAI supervisor had already developed a worship approach as a supervision model for improving the performance of PAI teachers, through working models solely because of God, working models as a means of communication with God, working models as a symbol of obedience to God, and the model of all work is valued as worship, and the model of work tirelessly. Even though this approach has been developed by PAI supervisors, it turns out that daily the PAI supervisors show mediocre attitudes and behavior in improving the performance of PAI teachers in public schools.